An introduction to the study of Justinian's Digest : containing an account of its composition and of the jurists used or referred to therein, together with a full commentary on one title (De usufructu) / Henry John Roby. - Roby, Henry John, 1830-1915 (Cambridge library collection. Classics., 2010)
Henry John Roby (1830-1915) was a Cambridge-educated classicist whose influential career included periods as a schoolmaster, a Professor of Roman law at University College, London, an educational reformer and a Member of Parliament. First published in 1884, this volume provides an analysis and discussion of Justinian's Digesta, a compendium of second and third century Roman legal writings which forms part of the body of Roman civil law issued under Justinian I in 533 AD. It is considered a fundamental work of Roman jurisprudence. Roby discusses the historical context of the Digesta, compares extracts in other legal sources with the original text and provides the Latin text of De Usufructu (one of the titles from the Digesta) with detailed close textual discussion and analysis. This volume was the first published guide to studying the Digesta and is considered one of Roby's most important contributions to jurisprudence.